A Face Concern Approach to Conflict Management – A Malaysian Perspective - Che Rose, Raduan; Uli, Jegak; Othman, Jamilah; Suppiah, Waitchalla R. (Science Publications, 2007)
This study presents a review of conflict management from a face concern approach. It presents the various definitions on conflict and types of conflict. It further looks at how face negotiation theory explains the use of various conflict management styles in individualist and collectivist cultures. In addition, it provides some insight into conflict management from a Malaysian perspective.